UPAYA UNI EROPA DALAM MEMPROMOSIKAN INTEGRASI SOSIAL ETNIS ROMA DI RUMANIA (2010-2014) - Sinaga, Elvina Chandra; Wiranata, I Made Anom; Kumala Dewi, Putu Ratih (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2015)
ABSTRAK This article describes the efforts of the European Union to promote Roma social integration in Romania since 2010 until 2014. Under descriptive-qualitative approach, this study mostly uses literature study technique. Conceptual framework that used are ethnicity, social discrimination, positive action and social integration promotion by international organization. The result of this research shows that European Union promotes Romania’s Roma social integration by providing positive action design, funding and giving administrative capacity support. Keywords: Social Discrimination, Romania’s Roma, Social Integration Promotion, European Union